2008
DOI: 10.3136/fstr.14.477
|View full text |Cite
|
Sign up to set email alerts
|

Durable Antihyperglycemic Effect of 6-O-Caffeoylsophorose with .ALPHA.-Glucosidase Inhibitory Activity in Rats

Abstract: To evaluate the duration of antihyperglycemic effects of 6-O-caffeoylsophorose (CS), a newly identified natural α-glucosidase inhibitor from fermented purple-sweet potato, a single oral administration of CS was given to maltose-loaded Sprague-Dawley rats. Administration of CS (200 mg/kg) 30 min or 60 min before maltose administration produced an elevation of blood glucose level by administration of 2 g/kg of maltose in rats that was significantly lower than for no administration (control). In contrast, simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…This revealed that pre‐administration of LG tea within 30 min, except for simultaneous administration, was effective in producing an acute antihyperglycaemic effect in the present SD rat experiments. In a previous report we showed that acarbose (3 mg kg −1 ) continued to have an ameliorative effect on BGL rise even when administered 120 min before maltose administration, along with the long‐term suppression of intestinal α‐glucosidase activity for up to 120 min 17. However, to clarify the mechanism underlying the durability of BGL reduction by LG tea for up to 30 min, further experiments, including intestinal α‐glucosidase activity, are now in progress.…”
Section: Resultsmentioning
confidence: 94%
“…This revealed that pre‐administration of LG tea within 30 min, except for simultaneous administration, was effective in producing an acute antihyperglycaemic effect in the present SD rat experiments. In a previous report we showed that acarbose (3 mg kg −1 ) continued to have an ameliorative effect on BGL rise even when administered 120 min before maltose administration, along with the long‐term suppression of intestinal α‐glucosidase activity for up to 120 min 17. However, to clarify the mechanism underlying the durability of BGL reduction by LG tea for up to 30 min, further experiments, including intestinal α‐glucosidase activity, are now in progress.…”
Section: Resultsmentioning
confidence: 94%
“…Peonidin 3-caffeoylsophoroside-5-glucoside (YGM-5b), and peonidin 3-dicaffeoylsophoroside-5-glucoside (YGM-4b), peonidin 3-caffeoyl-p-hydroxybenzoylsophoroside-5-glucoside (YGM-5a) and peonidin 3-caffeoyl-feruloylsophoroside-5-gluco-side (YGM-6) are major anthocyanins in the purple-fleshed sweet potato. The YGMs have not only high stability (6, 7) but also multifaceted biological actions including antioxidant capacity (6-9) and other functions (10,11) as well as antidiabetic effect (12)(13)(14)(15). In particular, the first finding that the acylated anthocyanins and their acylated moieties could lower the excess postprandial blood glucose level via R-glucosidase inhibition (13)(14)(15) led us to investigate antihyperglycemic potential of other acylated moieties from anthocyanins in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The YGMs have not only high stability (6, 7) but also multifaceted biological actions including antioxidant capacity (6-9) and other functions (10,11) as well as antidiabetic effect (12)(13)(14)(15). In particular, the first finding that the acylated anthocyanins and their acylated moieties could lower the excess postprandial blood glucose level via R-glucosidase inhibition (13)(14)(15) led us to investigate antihyperglycemic potential of other acylated moieties from anthocyanins in this study. In addition, caffeoylquinic acids are also known to exhibit antioxidant capacity (16,17), and other physiological functions including antihepatotoxic effect (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%